PERAWATAN KESEHATAN LANSIA DI INDONESIA - Mubasyir Hasanbasri (Populasi, 2000)
The role offamily inelderly care in Indonesia remainsfeasible solutionfor both economic andcultural reasons. Rapidsocio-economic changes have raised the concerns whetherfamily members can effectively meet the need ofelderly care. This study examines the relationship between household structure variables and the use of health services. We seek to learn the household structure characteristics that facilitate or constrain elderly care. If there is no constraint within the family,elderly people living dependently to their children will be less likely to show difference in health care practices as opposed to those living independently. The datafor this analysis is drawnfrom the 1993 Indonesian Socio-Economic Survey. Individuals aged 65 years or above reported to have illness complaints in the past two weeks and remained suffered when the survey was performed are included for the analysis.The finding sindicate that the elderly people living dependently with their children or with other families use less health care available outside their homes than those living independently.